The integration of expressive languages for childhood education - Naccari, Alba Giovanna Anna (Revista Eletrônica de Educação, 2024)
The recovery of the importance of school, after the suspension due to the covid emergency, sees at the centre of the training activities those that make children active subjects, capable of interacting concretely and creatively. The object of this paper is to describe some elements of how the integration of artistic languages, such as dance-movement, narration, and pictorial-plastic production, represents a significant contribution in this direction as a “left hand pedagogy” centred on imagination and creativity. At the basis of every expressive production there is the creative process that concerns and makes possible the development of our inner world and the increasingly awareness of the perception of the uniqueness of one's own being. These processes are enhanced and implemented by the suitably proposed integration of different languages. In this paper, the above synthetically outlined, I will be discussing a specific method of dance-movement-therapy proposed with a pedagogical method, defined in Italy as symbolic-anthropological. It is an approach tested in different contexts and schools of all levels, in which the different expressive possibilities are proposed in a fluid way in relation to a symbolic theme and to an educational objective. In the workshops in which the positivity of these activities was assessed, it emerged how those activities were particularly appropriate to children's needs. For kindergarten children, the immersive activities of movement, dance, drawing and storytelling, interactively integrated with each other, support: the process of inhabiting the body, perceptive discrimination, the possibility of putting order in one's emotions, the processes connected to the symbolic function and the gradual adaptation to reality. Furthermore, with primary school children, the activities satisfy, among other things, the need to give shape to one's internal world, as well as the need for competence and emotional channelling.